Development and validation of high resolution melting assays for high-throughput screening of BDNF rs6265 and DAT1 rs40184 - Faris, Asraa; Md Yusof, Hadri Hadi; Zainal Abidin, Shahidee; Habib, Omar; Cheah, Pike See; Stanslas, Johnson; Ibrahim, Normala; Lye, Munn Sann; Veerakumarasivam, Abhi; Rosli, Rozita; Ling, King Hwa (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: One of the commonly used techniques for mutation screening is High Resolution Melting (HRM) analysis. HRM is a post PCR method that relies on the detection of the fluorescent signals acquired due to the release of DNA intercalated dyes upon the melting of dsDNA to ssDNA. The method is simple, inexpensive and does not require post PCR-handling, making it suitable for high throughput screening. Methods: This study aimed to develop and validate HRM technique for the screening of two disease-associated single nucleotide polymorphisms (SNPs) namely BDNF rs6265 and DAT1 rs40184 using a total of 30 gDNA samples. The obtained results were confirmed and validated by sequencing. Results: HRM analysis showed that the predicted genotypes of BDNF rs6265 and DAT1 rs40184 among all the gDNA samples were in 100% concordance with the sequencing results, making it an accurate and sensitive method for the detection of SNPs. Conclusions: The application of HRM can accurately determine the genotype of BDNF rs6265 and DAT1 rs40184 SNPs, making it a promising tool for rapid and high-throughput screening of targeted SNPs in a large population study.